THE IMPACTS OF MENTIMETER-BASED ACTIVITIES ON EFL STUDENTS’ ENGAGEMENT IN INDONESIA - Sari, Angela Bayu Pertama (English Education Study Programme of Sanata Dharma University, Yogyakarta, Indonesia, 2021)
The effort to enhance students’ engagement in the EFL classroom is still becoming an issue. Fortunately, some studies have shown a positive correlation between technology utilization to elevate the students’ engagement. Based on that potential finding, this study aims at digging out the impact of Mentimeter, as one of the popular tools in this recent time, on EFL students’ engagement. It is a descriptive qualitative study. There are 70 respondents of the non-English students that were selected by using purposive sampling. The results of the study reveal that there are three most prominent students' positive perception towards the implementation of Mentimeter in the EFL classroom, namely practicality, anonymity, and freedom. Those three aspects foster the students to be engaged in the process of English learning. Then, most students perceive that no reason makes them dislike Mentimeter usage in the EFL classroom. The next finding depicts a significant impact of Mentimeter on the students’ engagement in English learning by giving opinions and discussion activities. It was proven with the percentage of students’ participation, reaching 82% and 91%, above the average of Mentimeter participants’ contribution.